Hepatitis A seroprevalence among infants aged 12 months in Ankara - Ince, Osman Tolga; Yalçin, S Songül; Yurdakök, Kadriye; Ozmert, Elif N (The Turkish Journal of Pediatrics, 2011)
Seroprevalence studies in various age groups contribute to a better understanding of hepatitis A infection and response to hepatitis A immunization. Hepatitis A seroprevalence in 12-month-old infants from Ankara was studied. Among 601 healthy infants, overall hepatitis A seropositivity was found to be 23.5%. There were no gender differences in seropositivity (22.6% for male and 24.5% for female infants). Although vaccination of infants would be an ideal prevention strategy, presence of maternal anti-hepatitis A virus (HAV) antibody interferes with the immune response to hepatitis A vaccine in infants and young children. Therefore, further knowledge about decay of maternal antibody in infants is important in determining the optimal age for vaccination against hepatitis A. There is no recommendation for routine hepatitis A vaccination in Turkey. However, we need more seroprevalence studies in different age groups to decide the appropriate timing/age of vaccination.